About the research of poem “Kissa Zhusip”. (Eurasian Journal of Philology Science and Education, 2015)
The review direction and primary source purposes of dastan "Kissa Zhusip", vision of decorative appearance, system of images of Persian is given to the version of authors "Zhusip and Zuleikh Ansari, Ferdousi, Zhami and Durbeka is given in the article. At the same time the author, based on the research of scientists about time of text writing of dastan`s genre, places of its real embodiment gives his appreciation. The author pays much attention to investigations of the Russian, Tatar, Turkish, Uzbek scientists and specialists in Turkic philology, carrying out bigscientific investigations in this direction. Besides the author, carrying out the comparative analysis of texts "Zhusip and Zuleikh", reveals essential changes and achievements in a statement of the vision by each author of work. His appreciation of the option written by Ali – simplicity and clearness to the ordinary reader. In simplicity, by words, the author the nationality as the main substantial idea and images are taken from Turkic folklore is looked through. Originality of a statement of idea of author`s work calls also that Ali in the creativity not blindly follows former Persian authors, and the knowncomposition writes special style – a quatrain where one of lines doesn't correspond to the general rhythmic outline.
Keywords: esthetics; bibliography; language features; dastan; idea; contents; style; tasks